Tailored therapy for Helicobacter pylori eradication: A systematic review and meta-analysis - Ma, Qin; Li, Hancong; Liao, Jing; Cai, Zhaolun; Zhang, Bo (Frontiers in Pharmacology, 2022)
BACKGROUND: With the increase of drug resistance, the eradication rate of H. pylori with empirical therapy declined. Tailored therapy has been proposed as an alternative to standard empirical treatments. The necessity of a personalized eradication therapy remains controversial. The aim of this study was to evaluate whether tailored therapy is superior to empirical therapy for H. pylori infection. METHODS: We searched eligible RCTs in PubMed, Embase (Ovid), Wangfang data and Cochrane Central Register of Controlled Trials published up to December 10, 2021. A random-effect model compared pooled relative risk (RR) with related 95% confidence intervals (CIs) was applied in meta-analysis. RESULTS: Twenty-two studies were included in the meta-analysis. In the first-line treatment, tailored therapy is more effective than empirical therapy (RR, 1.14 [95% CI, 1.08-1.21], I2=70.7%). In second-line or third-line therapy setting, no significant differences were found between the two treatments (RR, 1.06 [95% CI, 0.94-1.19], I2=71%). Regarding adverse events, no significant differences were found (RR, 0.92 [95% CI, 0.82-1.03], I2=36.7%). Most results were highly heterogeneous. CONCLUSION: Tailored therapies might achieve better eradication rates than empirical therapies in first-line therapy. There might be no obvious advantage in second-line or third-line treatment. Interpreting the results with high heterogeneity should still be cautious. Further clinical studies are needed and justified.